A STUDY ON NATIONAL CULTURAL VALUES, GDP PER CAPITA AND SOCIAL DEVELOPMENT LEVELS OF COUNTRIES (Third Sector Social Economic Review, 2022)
In this study, the effects of cultural values on the social progress levels of countries were investigated. GDP per capita was included in the research as a control variable since income is an important determinant of social progress. Then the effects of cultural values on social progress were analyzed with data from ninety-nine countries. Cultural values were examined by Hofstede's cultural dimensions of power distance, uncertainty avoidance, individualism-collectivism, masculinity-femininity, long-short term orientation, and indulgence-restrain. As well as the general social progress index score, social progress was also measured by the dimensions of basic human needs, foundations of wellbeing, and opportunity which forms social progress. For this reason, the effects of cultural values on the social progress index and its dimensions have been examined. The results of the research showed that at least one of the cultural dimensions of power distance, uncertainty avoidance, individualism, and long-term orientation significantly affected social progress. Uncertainty avoidance affected social progress, basic human needs, foundations of wellbeing, and opportunity; long-term orientation affected social progress and foundations of wellbeing; individualism and power distance affected social progress and opportunity dimension significantly. While power distance affected social progress negatively; uncertainty avoidance, individualism, and long-term orientation affected social progress positively.
Keywords: Cultural values; cultural dimensions; social progress; basic human needs; foundations of wellbeing